IoT Based ECG Using AD8232 and ESP32 - Bhattarai, Choodamani; Yadav, Siddhartha Kumar; Koirala, Subash (Nepal Journal of Science and Technology, 2022)
Good qualities ECG are utilized by physicians for interpretation and diagnosis of cardiovascular diseases. The rural hospitals of Nepal lack necessary equipment and need modern medical devices. This article is about an IoT-based ECG device in which AD8232 is used for the ECG signal acquisition, MATLAB for filtering and ESP32 for processing and communicating with the Internet.